LEGAL PROTECTION REGARDING PT SHOPEE INTERNATIONAL INDONESIA SELLERS IN CASH ON DELIVERY (COD) ONLINE TRANSACTIONS - Prabowo, Mafira Bimo Giri; Darmoko, Murry (YURIS: Journal of Court and Justice, 2025)
COD is a popular payment method in our society nowadays. However, this payment method may present additional risks for sellers, particularly related to the uncertainty of receiving payment and goods. This study aims to analyze legal protection for sellers in online transactions using the Cash on Delivery (COD) payment method at PT Shopee International Indonesia. The research employs a normative approach by examining relevant regulations, including the Consumer Protection Law and Shopee’s policies. The findings indicate that legal protection for sellers in the COD method is still suboptimal. A major challenge is the unclear responsibility between the platform, courier, and buyer. Additionally, there is a risk of loss for sellers when buyers refuse to accept goods or return them without valid reasons. Although Shopee provides some protective measures, such as complaint services and guarantees, the implementation and oversight of these protections need to be strengthened to minimize seller losses. This study recommends the need for clearer regulatory enforcement and closer cooperation among e-commerce platforms, the government, and sellers to ensure adequate legal protection for sellers in COD transactions.